Association between COMT SNP variation and timidity in Golden and Labrador Retrievers. (22nd June 2018) - Luo, D.; Ma, X.; Bai, J.; Zhou, Z.; Wang, F.; Wang, A.; Wang, J.
Summary: Timidity in dogs is a trait with high heritability. However, the relevant genetic factors and markers associated with this condition are largely unknown. The function of the catechol‐O‐methyl transferase ( COMT ) gene has been found to be associated with human fearful or anxious emotions, and the COMT :p.Val158Met polymorphism locus is significantly related to anxious behavior. In the present study, the correlation between timidity and four single nucleotide polymorphism (SNP) variations (C.‐1666C>G c.39A>G, c.216G>A, c.482G>A) of the COMT gene was investigated in dogs. The evaluation was based on the dog courage assessment assay and a genotype and haplotype analysis in Labrador Retrievers (LR) and Golden Retrievers (GR). The principal components analysis factor structure of the courage phenotype was invariant between LR and GR. Sex, breed and age had no statistically significant effect on the timidity of the dogs. All SNP loci detected were in Hardy–Weinberg equilibrium. The c.39A>G locus was removed in the subsequent association analysis due to the significant difference between LR and GR in genotype distributions. Intriguingly, the genotypes and haplotypes of the COMT gene were significantly and highly correlated with the timidity of LR and GR. The A alleles of the COMT :c.216G>A and c.482G>A loci appeared to play a dominant role in the timid behavior of the dogs. This result supports and broadens the warrior/worrier hypothesis and will have important implications for the understanding of the evolution of temperament in dogs. Additionally, the results provide predictive genetic markers for temperament in dogs.